Two magnetic phases in the co-sputtered Fe-Si3N4 thin film - Han, SM; Yu, SC; Kim, WT; Han, SH; Kim, HJ (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 1997)
The structure and magnetic properties of Fe-Si3N4 thin films fabricated by a co-sputtering technique mere studied by X-ray diffractometry and magnetometry. With increasing area fraction of Si3N4 pieces on Fe target, magnetization of the films decreased due to reduced Fe content and reduced grain size of bce crystalline phase, Temperature dependence and field dependence of magnetization of co-sputtered thin films can be explained bg a mixture of two types of particles showing paramagnetism and ferromagnetism.
Keywords: ALLOYS